Curb your enthusiasm: Agricultural growth in sub-Saharan Africa - Nin-Pratt, Alejandro; Johnson, Michael E.; Yu, Bingxin (International Food Policy Research Institute, 2013)
The evidence of improved performance of the agricultural sector in Sub‐Saharan Africa (SSA) in recent years has indeed been quite striking. For the first time, agricultural gross domestic product (AgGDP) per capita has maintained a real growth rate of 2.4 percent per year, while real AgGDP growth rates have exceeded 6 percent, a growth rate last seen in the 1970s. Similarly, performance of the overall economy, with average growth rates of 5.3 percent per year, has also been remarkable. In this context, Ghana has shown one of the best performing agricultural sectors in the region with AgGDP growing at more than six percent per capita in recent years.